The meanings of mystical dynamic ethics and its foundations in the works of Seyyed Heydar Amoli - Mohammad rasool Imani khoshkhoo (اخلاق وحیانی, 2022)
One of the characteristics mentioned for mystical ethics is its dynamism. In this article, by referring to the works of Seyyed Haider Amoli, one of the Shiite mystics and commentators of Ibn Arabi in the 8th century, an attempt has been made to examine the meaning of the dynamic of ethics in his works and to identify what this dynamic means and what are its ontological and anthropological foundations. According to Seyyed Haider's description of morals and moral virtues, dynamics can mean contingency and changeability of moral virtues depending on the level in which the seeker is located. Another meaning of the dynamic of ethics in Seyyed Haider's mysticism is the promotion of moral virtues towards the ceiling of human perfection and closeness to God. To explain the dynamics of ethics, Seyyed Haider has benefited from such things as the personal unity of existence, the connection of moral virtues with divine attributes, the inner nature of the path towards the truth, and the multilevel nature of the "heart".Paying attention to the ranking of virtues and their contingency in accordance with the situation and psychological and personality characteristics of people can play an important role in the effectiveness of moral education.